Choroidal nevus: a review of prevalence, features, genetics, risks, and outcomes. Issue 3 (May 2017) - Chien, Jason L.; Sioufi, Kareem; Surakiatchanukul, Thamolwan; Shields, Jerry A.; Shields, Carol L.
Abstract : Purpose of review: To review the prevalence, clinical features, imaging findings, cytogenetics, and risks and outcomes of choroidal nevus. Recent findings: Choroidal nevus is a benign melanocytic tumor, often discovered incidentally on ophthalmic examination. This lesion is generally well circumscribed and pigmented. The prevalence of choroidal nevus in postequatorial region in United States adults (≥40 years old) is approximately 5%. Choroidal nevus is associated with higher lifetime unopposed estrogen and greater BMI. In population-based evaluation, the mean nevus basal dimension is approximately 1.25 mm. Giant nevus (basal dimension ≥10 mm) carries greater risk for malignant transformation. Imaging modalities for evaluation of choroidal nevus include ultrasonography, fundus autofluorescence, and optical coherence tomography (OCT). Fluorescein angiography is occasionally employed to detect multifocal pinpoint leaks or choroidal neovascular membrane. Recently, OCT angiography demonstrated nevus with minimal overlying macular microvascular changes compared with melanoma. Cytogenetically, GNA11 or GNAQ mutations have been documented in uveal melanoma in 83% and in some cutaneous nevus subtypes. Further mutations lead to the development of melanoma at a rate of one of 8845 cases. Risk factors for transformation of nevus into melanoma are recalled by the mnemonic 'To find small ocular melanoma using helpful hints daily' representing thickness (T) more than 2 mm, subretinal fluid (F), symptoms (S) of flashes/floaters/blurred vision, orange (O) lipofuscin pigment, margin (M) less than 3 mm from optic disk, ultrasonographic hollowness (UH), halo (H) absence, and drusen (D) absence. The presence of three or more risk factors implies more than 50% chance for transformation to melanoma within 5 years. A new, online ocular oncology reading center can help judge nevus risk. Summary: Choroidal nevus is a common intraocular lesion, found predominantly in Whites. This mass carries a small risk (<1%) for malignant transformation. Patients with at least three risk factors should be evaluated for possible melanoma at an experienced ocular oncology center. Abstract : Supplemental Digital Content is available in the text